Price elasticities of electricity demand in Switzerland: Results from a household panel - Benjamin Volland; Ivan Tilov (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
In this paper, we use data from a new household-level panel survey to estimate short- and long-run price elasticities of residential electricity demand in Switzerland. We exploit Switzerland's unique local variation in topography-related grid maintenance costs and electricity taxation, to address endogeneity of average prices in our models. Using first difference and gradual adjustment models, we find short-run elasticities of -0.3 and long-run elasticities in excess of negative unity. Results thus suggest that a tax on electricity, as initially foreseen as a part of Switzerland's Energy Strategy 2050, is likely to have a moderate effect in the short run, but an important one in the long run.
Keywords: C23; D12; Q41; Q48; 330; Residential electricity demand; price elasticity; panel data; Switzerland